2021
DOI: 10.1097/mrr.0000000000000459
|View full text |Cite
|
Sign up to set email alerts
|

Can powered exoskeletons improve gait and balance in multiple sclerosis? A retrospective study

Abstract: Multiple sclerosis (MS) is a progressive neurologic disorder that can profoundly influence mobility, independence and quality of life. Gait dysfunction in MS is common, resulting in an increased risk of losing walking ability. Robotic exoskeletons have been developed to offer a new form of locomotor training. The aim of our study was to investigate the effectiveness of the powered exoskeleton (Ekso) in improving gait and balance in patients affected by MS. Twenty patients with MS (mean ± SD: age = 43.7 ± 10.3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…A total of 13 interventional studies reported data on quality of life/physical health quality of life for both interventional and control groups. 12,15,17,34,41,54 Pooling these studies, intervention using an exoskeleton appeared to improve the quality of life/physical health quality of life of participants (adjusted Hedges’g 0.58, 95% CI 0.28, 0.88; Figure 4).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 13 interventional studies reported data on quality of life/physical health quality of life for both interventional and control groups. 12,15,17,34,41,54 Pooling these studies, intervention using an exoskeleton appeared to improve the quality of life/physical health quality of life of participants (adjusted Hedges’g 0.58, 95% CI 0.28, 0.88; Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 46 studies, 26 responded to the inclusion criteria and provided sufficient. All 31 references were included in the systematic review, 6,12,41 and 27 presented sufficient statistical data to be included in the quantitative meta-analysis (Figure 1). 6,12,18,21,29,32,41…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations